Pengaruh Latihan Ball Handling Terhadap Peningkatan Keterampilan Dribbling Bola Basket Siswa Ekstrakurikuler SMPN 1 Tebing Tinggi - M Tegar; Daryono Daryono; Rury Rizhardi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to find out the influence of handling on the dribbling skills of basketball extracurricular students of SMPN I Tebing Tinggi. The research method used is the pseudo-experiment method, which is a study that is used to find the influence of certain behaviors on others under controlled conditions, other variables that can affect the experimental process can be strictly controlled. The population in this study amounted to 32 students with the sample used, namely 32 students with saturated sample technique (census). The data collection techniques used are tests and documentation. The data analysis technique used was a hypothesis test with the help of the SPSS 26 program. Based on the results of the hypothesis test calculations, a sig. value of 0.000 and a sig. p value of 0.05. Thus, it can be concluded that 0.000 < 0.05, then H0 is rejected and Ha is accepted or there is an effect of ball handling practice on the basketball dribbling skills of extracurricular students of SMPN I Tebing Tinggi. Based on the table above, the Pearson Correlation value is 0.665 where the value is in the high category.